A FIXED POINT THEOREM IN GENERALIZED D-SEMI METRIC SPACES - Mohamed, A A Sahib (Al-Nahrain Journal of Science, 2010)
The aim of this paper is to consider and study the concept of D-distance on a complete D-semi metric spaces and the fixed point theorem has been established on the D semi metric spaces.